2019
DOI: 10.3389/fpsyg.2019.02685
|View full text |Cite
|
Sign up to set email alerts
|

What Is Influencer Marketing and How Does It Target Children? A Review and Direction for Future Research

Abstract: Children nowadays spend many hours online watching YouTube videos in which their favorite vloggers are playing games, unboxing toys, reviewing products, making jokes or just going about their daily activities. These vloggers regularly post attractive and entertaining content in the hope of building a large follower base. Although many of these vloggers are adults, the number of child vloggers is flourishing. The famous child vlogger Ryan of Ryan’s World, for instance, has more than 19 million viewers and he is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
145
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(160 citation statements)
references
References 111 publications
(195 reference statements)
2
145
1
12
Order By: Relevance
“…Alternatively, source credibility theory asserts that if an endorser is perceived to be a credible source of information then consumers will likely develop a positive attitude towards the promoted product [29][30][31]. Source credibility is determined by several factors, including the perceived fit between the marketed product and the endorser, the likeability of the endorser, and the level of risk associated with adopting the endorser's behavior [32,33].Studies have yet to fully understand the extent to which children view influencers as role models or as credible sources of information.Although children's perception of influencer marketing of HFSS products specifically has not been explored, qualitative research has focused on their understanding of influencer marketing of non-food products [34][35][36]. Findings from these studies demonstrate that compared with other forms of digital marketing (e.g., YouTube pop-up advertisements), children (9 and 12 years) find influencer marketing via YouTubers to be less irritating because it does not interrupt media content, and provides useful product information (e.g., price) [36].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, source credibility theory asserts that if an endorser is perceived to be a credible source of information then consumers will likely develop a positive attitude towards the promoted product [29][30][31]. Source credibility is determined by several factors, including the perceived fit between the marketed product and the endorser, the likeability of the endorser, and the level of risk associated with adopting the endorser's behavior [32,33].Studies have yet to fully understand the extent to which children view influencers as role models or as credible sources of information.Although children's perception of influencer marketing of HFSS products specifically has not been explored, qualitative research has focused on their understanding of influencer marketing of non-food products [34][35][36]. Findings from these studies demonstrate that compared with other forms of digital marketing (e.g., YouTube pop-up advertisements), children (9 and 12 years) find influencer marketing via YouTubers to be less irritating because it does not interrupt media content, and provides useful product information (e.g., price) [36].…”
mentioning
confidence: 99%
“…Alternatively, source credibility theory asserts that if an endorser is perceived to be a credible source of information then consumers will likely develop a positive attitude towards the promoted product [29][30][31]. Source credibility is determined by several factors, including the perceived fit between the marketed product and the endorser, the likeability of the endorser, and the level of risk associated with adopting the endorser's behavior [32,33].…”
mentioning
confidence: 99%
“…8 Endorsement also includes "influencers" who promote products and brands through social media platforms, such as YouTube, Instagram, and Facebook, which reach millions of viewers or followers. 9 Marketing research has found that celebrity endorsement fosters brand awareness and brand loyalty among targeted consumers. 10 Public health experts suggest that celebrity endorsement is a type of integrated marketing communications (IMC) technique that is used to influence young people's diet-related cognitive, behavioral, and health outcomes through different media channels and platforms in diverse settings.…”
mentioning
confidence: 99%
“…A more recent example of a strategy to keep up with the youth of today is the use of social media which is both interactive and ubiquitous. It is the language and mode of communication that is most likely to target and reach a younger population (De Veirman et al, 2019;Lobstein et al, 2017;Yang and Xinyan, 2018). Due to the social isolation imposed by the COVID-19 pandemic in Brazil, there was an exponential growth in the use of e-commerce platforms selling alcoholic beverages.…”
mentioning
confidence: 99%